Occurrence of Harmful Cyanobacteria in Drinking Water from a Severely Drought-Impacted Semi-arid Region - Walter, Juline M.; Lopes, Fabyano A. C.; Lopes-Ferreira, Mônica; Vidal, Lívia M.; Leomil, Luciana; Melo, Fabiana; de Azevedo, Girlene S.; Oliveira, Rossandra M. S.; Medeiros, Alba J.; Melo, Adriana S. O.; De Rezende, Carlos E.; Tanuri, Amilcar; et al. (Frontiers in Microbiology, 2018)
Harmful cyanobacterial blooms have become increasingly common in freshwater ecosystems in recent decades, mainly due to eutrophication and climate change. Water becomes unreliable for human consumption. Here we report a comprehensive study carried out to investigate the water quality of several Campina Grande reservoirs. Our approach included metagenomics, microbial abundance quantification, ELISA test for three cyanotoxins (microcystin, nodularins and cylindrospermosin), and in vivo ecotoxicological tests with zebrafish embryos. Cytometry analysis showed high cyanobacterial abundance, while metagenomics identified an average of 10.6% of cyanobacterial sequences, and demonstrated the presence of Microcystis, Cylindrospermopsis and toxin coding genes in all ponds. Zebrafish embryos reared with pond water had high mortality and diverse malformations. Among the ponds analyzed, Araçagi showed the highest lethality (an average of 62.9% ± 0.8), followed by Boqueirão (lethality average of 62.5% ± 0.8). Here, we demonstrate that water from ponds undergoing extremely drought conditions have an abundance of potentially harmful cyanobacteria and their toxins. Our findings are consistent with a scenario in which polluted drinking water poses a great risk to human health.